Individual variation and repeatability of methane production from dairy cows estimated by the CO2 method in automatic milking system. (8th May 2015) - Haque, M. N.; Cornou, C.; Madsen, J.
Abstract : The objectives of this study were to investigate the individual variation, repeatability and correlation of methane (CH4 ) production from dairy cows measured during 2 different years. A total of 21 dairy cows with an average BW of 619±14.2 kg and average milk production of 29.1±6.5 kg/day (mean±s.d.) were used in the 1 st year. During the 2 nd year, the same cows were used with an average BW of 640±8.0 kg and average milk production of 33.4±6.0 kg/day (mean±s.d.). The cows were housed in a loose housing system fitted with an automatic milking system (AMS). A total mixed ration was fed to the cows ad libitum in both years. In addition, they were offered concentrate in the AMS based on their daily milk yield. The CH4 and CO2 production levels of the cows were analysed using a Gasmet DX-4030. The estimated dry matter intake (EDMI) was 19.8±0.96 and 23.1±0.78 (mean±s.d.), and the energy-corrected milk (ECM) production was 30.8±8.03 and 33.7±5.25 kg/day (mean±s.d.) during the 1 st and 2 nd year, respectively. The EDMI and ECM had a significant influence ( P <0.001) on the CH4 (l/day) yield during both years. The daily CH4 (l/day) production was significantly higher ( P <0.05) during the 2 nd year compared with the 1 st year. The EDMI (described by the ECM) appeared to be the key factor in the variation of CH4 release. A correlation ( r =0.54) of CH4 production was observed between the years. The CH4 (l/day) production was strongly correlated ( r =0.70) between the 2 years with an adjusted ECM production (30 kg/day). The diurnal variation of CH4 (l/h) production showed significantly lower ( P <0.05) emission during the night (0000 to 0800 h). The between-cows variation of CH4 (l/day, l/kg EDMI and l/kg ECM) was lower compared with the within-cow variation for the 1 st and 2 nd years. The repeatability of CH4 production (l/day) was 0.51 between 2 years. In conclusion, a higher EDMI (kg/day) followed by a higher ECM (kg/day) showed a higher CH4 production (l/day) in the 2 nd year. The variations of CH4 (l/day) among the cows were lower than the within-cow variations. The CH4 (l/day) production was highly repeatable and, with an adjusted ECM production, was correlated between the years.